All Days 2000
DOI: 10.2118/65165-ms
|View full text |Cite
|
Sign up to set email alerts
|

SWAG Injection on the Siri Field - An Optimized Injection System for Less Cost

Abstract: Simultaneous Water And Gas (SWAG) injection has been implemented on the Siri Field on the Danish Continental Shelf and represents the first reported full field application of its kind in the North Sea. The associated produced gas is mixed with injection water at the wellhead, and injected as a two-phase mixture. The required total injection volume for voidage replacement is thus achieved with a simplified injection system, fewer wells and reduced gas recompression pressure requirements. Injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The improved gas handling and oil recovery have been reported for SWAG injection at Siri field (Berg et al 2002 andQuale et al 2000), the Joffre Viking (Stephenson et al 1993) CO 2 miscible flood and SWAG emulation at the Rangely CO 2 miscible flood (Attanucci et al 1993). Pilot tests performed on Kuparuk River Field in Alaska Stoisits et al 1995) have also demonstrated the feasibility of SWAG injection.…”
mentioning
confidence: 87%
“…The improved gas handling and oil recovery have been reported for SWAG injection at Siri field (Berg et al 2002 andQuale et al 2000), the Joffre Viking (Stephenson et al 1993) CO 2 miscible flood and SWAG emulation at the Rangely CO 2 miscible flood (Attanucci et al 1993). Pilot tests performed on Kuparuk River Field in Alaska Stoisits et al 1995) have also demonstrated the feasibility of SWAG injection.…”
mentioning
confidence: 87%
“…The IOR has been reported for Simultaneous Water And Gas (SWAG) injection at Siri Field (Berge et al 2002;Quale et al 2000), the Joffre Viking CO 2 miscible flood (Stephenson et al 1993) and SWAG emulation at the Rangely CO 2 miscible flood (Attanucci et al 1993). Pilot tests performed in the Kuparul River Field in Alaska (Stoisits et al 1995;Ma et al 1995) have also demonstrated the feasibility of SWAG injection.…”
Section: Introductionmentioning
confidence: 92%
“…1 This design was derived from the lack of gas export and the ability to lower the gas compression pressure requirements by mixing it with water; however due to the mixture in the injected fluid (ca. 0.5% CO 2 in the water, high pressure and therefore high partial pressure of CO 2 ) together with oxygen content created several corrosion issues.…”
Section: Review Of the Problemmentioning
confidence: 99%